Factors Affecting Medical Record Service Quality Activities at Puskesmas Bestari - Siti Permata Sari Lubis (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Factors that affect the quality of medical record services are human resources, facilities and infrastructure and policy monitoring and evaluation. The problem of this study is that there are less medical record officers, causing less fast service. The purpose of the study was to determine the factors that affect the quality of medical record service activities at Puskesmas Bestari. This type of research is a descriptive study where the population and sample are the same, namely 4 general practitioners, 3 dentists, 7 nurses and 2 medical record officers. This research collection technique is a field study technique, namely questionnaires, interviews and observations. The data analysis used in this study was univariate analysis. The results obtained were poor service quality by 12.5%, poor doctor human resources by 28.6%, poor nurse resources by 28.6%, good medical recorder resources by 66.6%, poor facilities and infrastructure by 20%, policy monitoring and evaluation by 40%. Based on these results, it can be concluded that the quality of medical record services, doctor human resources, nurse human resources, medical recorder human resources, facilities and infrastructure and policy monitoring and evaluation are still lacking, so it is expected that the Head of the Puskesmas will conduct training on the importance of the quality of medical record services in improving the performance of officers at the Puskesmas.